HUBUNGAN ANTARA KECEMASAN DAN MOTIVASI BELAJAR PADA MAHASISWA PERTUKARAN PELAJAR - Natalia Dende; Raden Ayu Karimatu Zakiyah; Pamela Hendra Heng; Debora Basaria (STKIP Subang, 2025)
Exchange students face various challenges, one of which is anxiety that can affect their learning motivation. This study aims to determine the relationship between anxiety and learning motivation among exchange students. This research employs a quantitative method, with data collection techniques in the form of questionnaires. The measurement tools used are the State-Trait Anxiety Inventory (STAI) to measure the level of anxiety and the Academic Motivation Scale (AMS) to measure learning motivation. The participants in this study consisted of 101 exchange students who filled out the questionnaire. This study is expected to serve as a basis for psychological interventions that support the well-being and academic achievement of exchange students.